Recovery of acmopolynema hervali parasite from mahanarva posticata eggs, in Carpina, Pe, Brazil - Marques, E. J.; Boas, A. M. Vilas (Pesquisa Agropecuaria Brasileira, 2014)
In 1969, an attempt was made in Pernambuco, Brazil, to introduce the Acmopolynema hervali wasp. About 800 adults from Teresópolis and Niterói, RJ, were released at the Estação Experimental de Cana-de-Açúcar do Cabo (Sugarcane Experimental Station of Cabo), PE, Brazil. The first parasites, which emerged from M. posticata eggs, were recovered in August 1972 from the same station although in small percentage. In 1978 the A. hervali wasp programme was restarted by the utilization of parasite Mahanarva rubicunda indentata and M. posticata eggs, from Magé and Campos, RJ. So, it was possible to release 1,026 males and 1,884 females of the wasp at sugarcane fields to the Experimental Station, of Carpina, and 138 males and 51 females in the Usina Central de Barreiros (Central Barreiros Sugar Mill), This took place in 1978 and 1979. However, during this period no parasites were recovered. Recently, in november 1983, adults of A. hervali, from M. posticata eggs, collected on Sugarcane fields on the Experimental Station of Carpina, emerged in the laboratory. Thereby a parasitism of 15.4% was registered, by observing 1,707 M. posticata eggs, the emergence of which, was 44 females and 67 males of A. hervali wasps.